2011
DOI: 10.1590/s1519-566x2011000100013
|View full text |Cite
|
Sign up to set email alerts
|

Ovary Development and Maturation in Nezara viridula (L.) (Hemiptera: Pentatomidae)

Abstract: Ovary development and maturation of Nezara viridula (L.) were evaluated by examining ovariole morphology and the alterations in the biochemical (protein synthesis related to reproduction) composition of the hemolymph. Quantitative and qualitative protein analyses were performed and ovary structural alterations for the pre-reproductive and reproductive stages were recorded. Total concentration of proteins in female hemolymph gradually increased until the end of the pre-mating stage, remaining unaltered thereaft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…The ovaries of D. melacanthus are telotrophic and meroistic, containing a trophic region (tropharium) with a germarium and nurse cells, vitellarium cells with oocytes ( Figure 1A-1C), apical filaments and a pedicel; these anatomical features are found in insects of the same family, as described by other authors (CHAPMAN, 1998;KUGLER et al, 2006;OGORZAŁEK;TROCHIMCZUK, 2009;FORTES et al, 2011;GOMES et al, 2013). In the tropharium, in the ovariole distal region, oocytes and nurse cells are formed, which were also observed in D. melacanthus ( Figure 1A-1C).…”
Section: Ovariole Analysessupporting
confidence: 76%
“…The ovaries of D. melacanthus are telotrophic and meroistic, containing a trophic region (tropharium) with a germarium and nurse cells, vitellarium cells with oocytes ( Figure 1A-1C), apical filaments and a pedicel; these anatomical features are found in insects of the same family, as described by other authors (CHAPMAN, 1998;KUGLER et al, 2006;OGORZAŁEK;TROCHIMCZUK, 2009;FORTES et al, 2011;GOMES et al, 2013). In the tropharium, in the ovariole distal region, oocytes and nurse cells are formed, which were also observed in D. melacanthus ( Figure 1A-1C).…”
Section: Ovariole Analysessupporting
confidence: 76%
“…pRNAi response, since both Coleoptera and Hemiptera have telotrophic meroistic ovarioles (Klowden, 2008). Newly molted stinkbug females have undeveloped ovaries, and the ovary development seems to proceed at the same rate regardless of whether the female has mated or not (Fortes et al, 2011). The pre-mating and pre-oviposition periods seem to vary based on the species, with the pre-mating period lasting up to ten days with pre-oviposition periods of up to two weeks (Fortes et al, 2011;Silva et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Newly molted stinkbug females have undeveloped ovaries, and the ovary development seems to proceed at the same rate regardless of whether the female has mated or not (Fortes et al, 2011). The pre-mating and pre-oviposition periods seem to vary based on the species, with the pre-mating period lasting up to ten days with pre-oviposition periods of up to two weeks (Fortes et al, 2011;Silva et al, 2011). Similarly in WCR, the pre-oviposition period lasts between 12 and 15 days (Branson and Johnson, 1973;Hill, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…[16] revealed that maturation of ovaries in female insects are normally correlated with age until sexual maturity is reached. Correlations of ovarian development with female age are well established in insects [17]. [18] worked on the ladybird beetle Propylea dissecta (Coleoptera : Coccinellidae) and stated that mating accelerated ovarian development, and that increase in age led to increase in number of follicles, ovarian width, number of mature eggs and egg loads.…”
Section: Discussionmentioning
confidence: 99%